More best practices for elementary classrooms : what award-winning teachers do - Stone, Randi (Thousand Oaks, Calif. : Corwin Press ; [Alexandria, Va.] : National Association of Elementary School Principals, 2009)
Part II: Teaching reading and writing : Teaching reading : The elementary teacher-librarian: a job defined by the needs of the school / Peggy J. Billiard, grades k-5 (Indiana) -- Total physical response (TPR): learning vocabulary through movement / Jodi Jari, grades 1-5, ESL (Wisconsin) -- Nonfiction guided reading lesson / Maranda Alcala, grades 2-3 (Oregon) -- Reading assessment menu / Reid Nunn, grades 4-5 (New Mexico) -- Nonfiction electronic book / Karen Ann Brown, grades 4-5+ (Colorado) -- Teaching writing : Kindergarten authors / Renee Borden, kindergarten (Tennessee) -- Teaching writing: what works / Nikki Salvatico, grades k-2 (Pennsylvania) -- Succeeding with reading and writing instruction for multilevel classrooms / Kendra Jiles, grades k-5 (South Carolina) -- Multigenre writing / Karen Ann Brown, grades 4-5+, gifted (Colorado) -- Creating villains to create great narratives / Andrea Payan, grades 4-5 (Wisconsin) -- Breakfast biographies / Tammy Spratt, grades 4-5 (Kentucky) -- An inquiry approach to writing memoir / Stacy Gardner Dibble, grades 4-5 (Minnesota) -- Found poetry / Kim Tredick, grade 5 (California) -- The "big" poem / Sue Davis Pope, grade 5 (Utah) -- Part IV: Teaching social studies, music, art, and physical education : Teaching social studies : Cultural diversity in our community: past and present : Christopher R. Shadle, grades k-4 (Ohio) -- Prejudice against African Americans during the time of segregation / Kim Heckart, grade 3 (Iowa) -- Current events: learning about our world / Karen Ann Bowen, grades 4-5+, gifted (Colorado) -- Inaugural poetry through elementary school publications / Luella L. Atkins, grades 4-5+ (Missouri) -- How simulations and impersonations inspire students / Heather E. Robinson, grade 5 (Arizona) -- Archi-techs: learning U.S. history through architecture / Eileen Biegel, grade 5 (Florida) -- Immigration: was your name changed at Ellis Island? / Tammy Spratt, grade 5 (Kentucky) -- Teaching music, art, and physical education : Celebrating music / Heather Robinson, grades 4-5+ (Arizona) -- A taste of music: concert ideas / Denese Odegaard, grade 5 (North Dakota) -- Progressive portraits / Susan Menkes, grades k-6 (New York) -- The motor lab and sensory tools for the classroom / Cindy L. Hodgeson, grades k-4 (Arizona) -- Brain exercises / Tammy Haggerty Jones, grades k-5 (Illinois).
Classroom management, scheduling, and community involvement -- Differentiating instruction in regular and inclusive classrooms -- Using technology in the classroom -- Teaching science -- Teaching math -- Teaching reading -- Teaching writing -- Teaching social studies -- Teaching music, art, and physical education.
Includes bibliographical references.
Keywords: Elementary school teachers -- United States -- Case studies; Elementary school teaching -- United States -- Case studies